(x+1)+2(x-3)-5=(x+2)-(x+3)+2

Simple and best practice solution for (x+1)+2(x-3)-5=(x+2)-(x+3)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+1)+2(x-3)-5=(x+2)-(x+3)+2 equation:


Simplifying
(x + 1) + 2(x + -3) + -5 = (x + 2) + -1(x + 3) + 2

Reorder the terms:
(1 + x) + 2(x + -3) + -5 = (x + 2) + -1(x + 3) + 2

Remove parenthesis around (1 + x)
1 + x + 2(x + -3) + -5 = (x + 2) + -1(x + 3) + 2

Reorder the terms:
1 + x + 2(-3 + x) + -5 = (x + 2) + -1(x + 3) + 2
1 + x + (-3 * 2 + x * 2) + -5 = (x + 2) + -1(x + 3) + 2
1 + x + (-6 + 2x) + -5 = (x + 2) + -1(x + 3) + 2

Reorder the terms:
1 + -6 + -5 + x + 2x = (x + 2) + -1(x + 3) + 2

Combine like terms: 1 + -6 = -5
-5 + -5 + x + 2x = (x + 2) + -1(x + 3) + 2

Combine like terms: -5 + -5 = -10
-10 + x + 2x = (x + 2) + -1(x + 3) + 2

Combine like terms: x + 2x = 3x
-10 + 3x = (x + 2) + -1(x + 3) + 2

Reorder the terms:
-10 + 3x = (2 + x) + -1(x + 3) + 2

Remove parenthesis around (2 + x)
-10 + 3x = 2 + x + -1(x + 3) + 2

Reorder the terms:
-10 + 3x = 2 + x + -1(3 + x) + 2
-10 + 3x = 2 + x + (3 * -1 + x * -1) + 2
-10 + 3x = 2 + x + (-3 + -1x) + 2

Reorder the terms:
-10 + 3x = 2 + -3 + 2 + x + -1x

Combine like terms: 2 + -3 = -1
-10 + 3x = -1 + 2 + x + -1x

Combine like terms: -1 + 2 = 1
-10 + 3x = 1 + x + -1x

Combine like terms: x + -1x = 0
-10 + 3x = 1 + 0
-10 + 3x = 1

Solving
-10 + 3x = 1

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '10' to each side of the equation.
-10 + 10 + 3x = 1 + 10

Combine like terms: -10 + 10 = 0
0 + 3x = 1 + 10
3x = 1 + 10

Combine like terms: 1 + 10 = 11
3x = 11

Divide each side by '3'.
x = 3.666666667

Simplifying
x = 3.666666667

See similar equations:

| ln(5x+3)=4 | | 27-3(2x+3)=2(1-3x) | | 7-n-6=-13+6n | | 12x^2+9x-20=0 | | 5(2.6x+3.9)=5 | | cos(2x)-5cosx+3=o | | .5x+7=2x+14 | | 1-4=7 | | 18-8(x+2)=2(x-9) | | 3x+5=-6x+32 | | -2/5(5x-20y) | | 2x^2+8x+n=15+n | | -(ln)(2)/x=91.2 | | F(x)=x^4+6x^3+9x^2 | | x+7*2=122 | | x+7*2= | | 3n^2+4n-4=0 | | -4/3(33=n)=12=n | | 10x-30=10 | | x+2*(x+2+2x-8)=x+1*(x+1+2x-5) | | 14x-14-4+6=0 | | (3x-1)-5(x+2)(x-2)+12=6+(2x+3) | | x^2+2xy+y^2=0ratio | | 3n^2+3n-36=0 | | 3k+16=5k+20 | | -10a+25a+5a=-40 | | f=9*6 | | 37=5a-4a-3 | | 3x^2-25x-28= | | 7x(2x+3)=0 | | f=9/6 | | 2(n+4)-(3n+1)=5 |

Equations solver categories